1991
DOI: 10.1346/ccmn.1991.0390411
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of 1-Aminonapththalene at the Surface of Smectite Clays

Abstract: Abstract--One-aminonaphthalene is sorbed onto the Na-saturated smectite clays, montmorillonite and hectorite, by cation exchange. In the presence of Fe 3 § either in the clay structure or on the clay surface, sorption is followed by the formation of a blue-colored complex, with the continuous disappearance of aminonaphthalene from solution and the clay surface. The rate of aminonaphthalene disappearance decreases as pH increases. With time, four major products that appear to be structural isomers of N(4-aminon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…It is possible that changes in structure and surface charge during the course of reaction affect the reaction rate on nontronite. Since the reaction did not proceed on hectorite, which is iron free, it is reasonable to assume that iron can be the electron acceptor in montmorillonite as has been argued previously (25). In this instance, we assume that the reduction is almost entirely of octahedral Fe-O-Al, based on the much lower quantity of iron in SWy-1 relative to NG-1.…”
Section: Discussionmentioning
confidence: 94%
“…It is possible that changes in structure and surface charge during the course of reaction affect the reaction rate on nontronite. Since the reaction did not proceed on hectorite, which is iron free, it is reasonable to assume that iron can be the electron acceptor in montmorillonite as has been argued previously (25). In this instance, we assume that the reduction is almost entirely of octahedral Fe-O-Al, based on the much lower quantity of iron in SWy-1 relative to NG-1.…”
Section: Discussionmentioning
confidence: 94%
“…The concentration of Mn(II) used in each system was based on corresponding loadings of Mn oxide in the Mn-Mts. We assume MB oxidation by uncoated Na-Mt negligible in time scale of the experiments, though it has been reported that iron-bearing montmorillonite can oxidize phenols and aromatic amines, for instance, in a long duration [39]. The oxidation of Mn(II) ions by O 2 in the uncoated Na-Mt system during the experiments was expected trivial because of slow kinetics in acidic solution.…”
Section: Oxidative Decolorization Of Mbmentioning
confidence: 99%
“…The sorption and transformation of aminonaphthalene has previously been reported as relatively rapid (98% in 24 h) in a batch system with an excess number of sites (3). In situations where the number of transformation sites was not in excess or there was a stoichiometric balance of reactants, the observed rate of approach to equilibrium might be considerably slower.…”
Section: Introductionmentioning
confidence: 97%